Electromyographic and laboratory findings in acute Solanum torvum poisoning*. (2nd January 2016) - Glover, Robert L.; Connors, Nicholas J.; Stefan, Cristiana; Wong, Ernest; Hoffman, Robert S.; Nelson, Lewis S.; Milstein, Mark; Smith, Silas W.; Swerdlow, Michael
Abstract: Context : Solanum torvum berries, known as susumber or turkey berries, are prepared as part of traditional Jamaican dishes usually served with cod and rice. Poisoning is rare. Although toxic compounds have never been definitively isolated, previous reports suggest toxicity results from inhibition of acetylcholinesterases. We present a case of susumber berry poisoning with detailed electromyographic studies and laboratory analysis. Case details : A 54-year-old woman presented to the Emergency Department (ED) complaining of vision, speech, and gait changes; emesis; and diffuse myalgias following consumption of susumber berries. The physical examination demonstrated an intact, lucid mental status, miosis, opsoclonus, severe dysarthria, dysmetria, mild extremity tenderness and weakness, and inability to ambulate. Her symptom constellation was interpreted as a stroke. Discussion : Electromyography demonstrated a pattern of early full recruitment as well as myotonia during the period of acute toxicity. Additionally, solanaceous compounds, in particular solasonine and solanidine, were identified in leftover berries and the patient's serum. Store-bought commercial berries and subsequent serum samples were free of such toxic compounds. EMG studies, together with a laboratory analysis of berries or serum can assist in the differential diagnosis of stroke, and provide both a prognostic screening and confirmation of suspected glycoside toxicity.